American independent cinema : an introduction - Tzioumakis, Yannis (Edinburgh : Edinburgh University Press, 2017)
This introduction to American Independent Cinema offers both a comprehensive industrial and economic history of the sector from the early twentieth century to the present and a study of key individual films, filmmakers and film companies.
Introduction : problems of definition and the discourse of American independent cinema -- Part 1. American independent cinema in the studio years (mid-1920s-late 1940s). 1. Independent filmmaking in the studio era : tendencies within the studio system -- 2. Independent filmmaking in the studio era : the Poverty Row studios (1930-50s) -- Part 2. American independent cinema in the post-studio era (late 1940s-late 1960s). 3. Independence by force : the effects of the Paramount Decree on independent film production -- 4. An audience for the independents : exploitation films for the nation's youth -- Part 3. American independent cinema and the 'New Hollywood' (late 1960s to late 1970s). 5. The new Hollywood and the independent Hollywood -- 6. American independent cinema in the age of the conglomerates -- Part 4. Contemporary American independent cinema (1980s to date) -- 7. Mini-majors and major independents -- 8. The institutionalisation of American independent cinema -- 9. American independent cinema in the age of media convergence -- Epilogue : from independent to 'specialty' cinema.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed November 16, 2018).
JSTOR
Keywords: Independent filmmakers -- United States -- Case studies; Independent films -- Economic aspects -- United States; Independent films -- United States -- History and criticism; Motion picture industry -- United States -- History -- 20th century; Cinéastes indépendants -- États-Unis -- Études de cas; Films indépendants -- Aspect économique -- États-Unis.; Films indépendants -- États-Unis -- Histoire et critique; Cinéma -- Industrie -- États-Unis -- Histoire -- 20e siècle.; PERFORMING ARTS -- Reference; Independent filmmakers; Independent films; Motion picture industry; United States; 1900-1999; Case studies; Criticism, interpretation, etc; History